The maidens - Michaelides, Alex, 1977- (New York, NY : Celadon Books, 2021)
"Edward Fosca is a murderer--of this Mariana is certain. But Fosca is untouchable. A handsome and charismatic Greek tragedy professor at Cambridge University, Fosca is adored by staff and students alike-particularly by the members of a secret society of female students known as The Maidens. Mariana Andros is a brilliant but troubled group therapist who becomes fixated on The Maidens when one member, a friend of Mariana's niece Zoe, is found murdered in Cambridge. Mariana, who was once herself a student at the university, quickly suspects that behind the idyllic beauty of the spires and turrets, and beneath the ancient traditions, lies something sinister."--
Keywords: College teachers -- Fiction; Teacher-student relationships -- Fiction; Murder -- Investigation -- Fiction; Murderers -- Fiction; Secret societies -- Fiction; Group psychotherapy -- Fiction; Psychotherapists -- Fiction; Psychological fiction; Thrillers (Fiction)